Breast cancer incidence and mammography screening among resettlers in Germany - Simone Kaucher; Laura Khil; Hiltraud Kajüter; Heiko Becher; Maren Reder; Petra Kolip; Jacob Spallek; Volker Winkler; Eva-Maria Berens (BMC, 2020)
Abstract Background European studies showed that women with a migration background are less likely to participate in mammography screenings than autochthonous women. However, the participation in the German mammography screening programme (MSP) among ethnic German migrants from countries of the former Soviet Union (called resettlers) is unclear so far. The aim of this study was to identify possible differences regarding MSP participation between resettlers from the FSU and the general German population. Methods Data from two independent, complementary studies from North Rhine-Westphalia, Germany (a retrospective cohort study 1994-2013; a cross-sectional study 2013/14) were used for comparisons between resettlers and the general population: Odds Ratios (ORs) for MSP participation utilizing the cross-sectional data and time trends of breast cancer incidence rates as well as Chi-Square tests for breast cancer stages utilizing the cohort data. Results Resettlers showed higher Odds to participate in the MSP than the general population (OR 2.42, 95% CI 1.08-5.42). Among resettlers, a large increase in incidence rates was observed during the MSP implementation (2005-2009), resulting in stable and comparable incidence rates after the implementation. Furthermore, pre-MSP implementation, the proportion of advanced breast cancer stages was higher among resettlers than in the German population, post-MSP implementation the proportion was comparable. Conclusions MSP participating seems surprisingly high among resettlers. An explanation for the increased willingness to participate might be the structured invitation procedure of the MSP. However, the exact reasons remain unclear and future research is needed to confirm this hypothesis and rule out the possibility of selection bias in the cross-sectional study.